Zapisz w jak najprostszej postaci.

a) 2a(b-3) - 2b(a-3)
b) a(a+b) + a(a-b) + b(b+a) + b(b-a)
c) 5a(a-2) + 2a(a+5)
d) 3(a + 2b - 3c) - 2(a - 2c) + 5(c - b) - (a+b)
e) 8x(x+y) - 2y(y - x) + ½(6x² + 8x²) - 2(y² + 5xy)
f) ½a(a + 1) - 2 (a²/4 - a/2)
g) ⅓a(a + 1) - 4 (⅓a² - 1/12a) - a(1 - a)
h) 0,2(5a + 10b) - 7(0,1a - b) + a - b

2

Odpowiedzi

2010-03-03T16:58:23+01:00
  • pewi
  • Początkujący
2010-03-03T17:02:20+01:00
^ oznacza do kwadaru
a) 2a(b-3) - 2b(a-3) = 2ab-6a-2ab+6 = -6a+6 = -6(a-1)
b) a(a+b) + a(a-b) + b(b+a) + b(b-a) = a^+ab+a^-ab+b^-ab = 2a^+b^-ab
c) 5a(a-2) + 2a(a+5) = 5a^-10a+2a^+10 = 7a^-10a+5
d) 3(a + 2b - 3c) - 2(a - 2c) + 5(c - b) - (a+b) = 3a+6b-9c-2a+4c+5c-5b=a+b-4c
e) 8x(x+y) - 2y(y - x) + ½(6x² + 8x²) - 2(y² + 5xy)=
8x^+8xy-2y^+2xy+7x^-2y^-10xy= 15x^-4y^
f) ½a(a + 1) - 2 (a²/4 - a/2)= (a^/2) + 1/2-(a^/2)+a= a+1/2
g) ⅓a(a + 1) - 4 (⅓a² - 1/12a) - a(1 - a)= (a^/2) + 1/2 -(4a^/3)+ (3/a)-a+a^=
(a^/6)-a+1/2
h) 0,2(5a + 10b) - 7(0,1a - b) + a - b= a+2b-0,7a+7b+a-b= 1,3a+8b
11 3 11